Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the exact value of [tex]\(\tan \frac{5 \pi}{12}\)[/tex], we can use the half-angle identities. Recall that the half-angle identity for tangent is given by:
[tex]\[ \tan \frac{\theta}{2} = \frac{1 - \cos{\theta}}{\sin{\theta}} \][/tex]
or alternatively,
[tex]\[ \tan \frac{\theta}{2} = \frac{\sin{\theta}}{1 + \cos{\theta}} \][/tex]
Firstly, let's begin by rewriting [tex]\(\frac{5 \pi}{12}\)[/tex] in terms of a known angle using the sum of angles identity. Notice that:
[tex]\[ \frac{5 \pi}{12} = \frac{\pi}{4} + \frac{\pi}{6} \][/tex]
Now we use the tangent addition formula:
[tex]\[ \tan (A + B) = \frac{\tan A + \tan B}{1 - \tan A \tan B} \][/tex]
Let [tex]\( A = \frac{\pi}{4} \)[/tex] and [tex]\( B = \frac{\pi}{6} \)[/tex].
We know:
[tex]\[ \tan \frac{\pi}{4} = 1 \quad \text{and} \quad \tan \frac{\pi}{6} = \frac{1}{\sqrt{3}} \][/tex]
Substitute these into the tangent addition formula:
[tex]\[ \tan \left(\frac{\pi}{4} + \frac{\pi}{6}\right) = \frac{\tan \frac{\pi}{4} + \tan \frac{\pi}{6}}{1 - \tan \frac{\pi}{4} \tan \frac{\pi}{6}} = \frac{1 + \frac{1}{\sqrt{3}}}{1 - 1 \cdot \frac{1}{\sqrt{3}}} = \frac{1 + \frac{1}{\sqrt{3}}}{1 - \frac{1}{\sqrt{3}}} = \frac{\frac{\sqrt{3} + 1}{\sqrt{3}}}{\frac{\sqrt{3} - 1}{\sqrt{3}}} = \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \][/tex]
We further simplify this by rationalizing the denominator:
[tex]\[ \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \times \frac{\sqrt{3} + 1}{\sqrt{3} + 1} = \frac{(\sqrt{3} + 1)^2}{(\sqrt{3} - 1)(\sqrt{3} + 1)} = \frac{3 + 2\sqrt{3} + 1}{3 - 1} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \][/tex]
Therefore, the exact value of [tex]\(\tan \frac{5 \pi}{12}\)[/tex] is:
[tex]\[ C) 2 + \sqrt{3} \][/tex]
[tex]\[ \tan \frac{\theta}{2} = \frac{1 - \cos{\theta}}{\sin{\theta}} \][/tex]
or alternatively,
[tex]\[ \tan \frac{\theta}{2} = \frac{\sin{\theta}}{1 + \cos{\theta}} \][/tex]
Firstly, let's begin by rewriting [tex]\(\frac{5 \pi}{12}\)[/tex] in terms of a known angle using the sum of angles identity. Notice that:
[tex]\[ \frac{5 \pi}{12} = \frac{\pi}{4} + \frac{\pi}{6} \][/tex]
Now we use the tangent addition formula:
[tex]\[ \tan (A + B) = \frac{\tan A + \tan B}{1 - \tan A \tan B} \][/tex]
Let [tex]\( A = \frac{\pi}{4} \)[/tex] and [tex]\( B = \frac{\pi}{6} \)[/tex].
We know:
[tex]\[ \tan \frac{\pi}{4} = 1 \quad \text{and} \quad \tan \frac{\pi}{6} = \frac{1}{\sqrt{3}} \][/tex]
Substitute these into the tangent addition formula:
[tex]\[ \tan \left(\frac{\pi}{4} + \frac{\pi}{6}\right) = \frac{\tan \frac{\pi}{4} + \tan \frac{\pi}{6}}{1 - \tan \frac{\pi}{4} \tan \frac{\pi}{6}} = \frac{1 + \frac{1}{\sqrt{3}}}{1 - 1 \cdot \frac{1}{\sqrt{3}}} = \frac{1 + \frac{1}{\sqrt{3}}}{1 - \frac{1}{\sqrt{3}}} = \frac{\frac{\sqrt{3} + 1}{\sqrt{3}}}{\frac{\sqrt{3} - 1}{\sqrt{3}}} = \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \][/tex]
We further simplify this by rationalizing the denominator:
[tex]\[ \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \times \frac{\sqrt{3} + 1}{\sqrt{3} + 1} = \frac{(\sqrt{3} + 1)^2}{(\sqrt{3} - 1)(\sqrt{3} + 1)} = \frac{3 + 2\sqrt{3} + 1}{3 - 1} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \][/tex]
Therefore, the exact value of [tex]\(\tan \frac{5 \pi}{12}\)[/tex] is:
[tex]\[ C) 2 + \sqrt{3} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.